Comparing Stage Presence and Virtual Reality Presence - Samur (University of Toronto – Toronto, Canada), Sebastian Xavier (Revista Brasileira de Estudos da Presença, 2022)
Reflecting on the impending release of new Head Mounted Display virtual reality (VR) technologies, the article examines definitions and techniques for digital presence, and compares them with research into stage presence. It opens with an outline of definitions of digital presence, comparing them with Cormac Power’s fictional, auratic, and literal modes of presence in performance. The article then looks at techniques used in VR and on stage to achieve presence. Finally, performance examples that use virtual reality technologies are presented. The article concludes that even if the technology falls short, discourse on digital presence is useful in providing insights into presence on stage.